Analisis Berdirinya Negara Islam Pakistan Dalam Perkembangan Sejarah Islam Di Indonesia - Priatna, Gana (Jurnal Dewantara, 2017)
Islamic State of Pakistan was inaugurated on August 15, 1947 as a state for the Muslims of India. Efforts to establish Pakistan as a state is not separated from the role of Islamic leaders of Pakistan through the Islamic organizations that exist at the time. Since the fall of the Mughal Dynasty (1857) and the entry of British rule in India. The Muslims as a minority population was received unfair treatment from the British rulers and among the ummah Hindus as the majority population in India caused menculnya the ideas and thoughts of the prominent fig-ures of Indian Islam, like, Shah Wali Allah, Sayyid Ahmad Sayyid, Sayyid Ahmad Khan, Muhammad Iqbal and Muhammad Ali Jinnah, seeks to establish a separate Islamic government, which gave birth to the State of Pakistan.